Characterization of novel insect cytochrome P450-fusion enzymes - Talmann, Lea; Justus Liebig University Giessen (My University, 2016)
Cytochrome P450 monooxygenases (P450s) represent a ubiquitous group of enzymes with a broad substrate spectrum. Their ability to catalyze a variety of reactions, e.g. detoxification of insecticides, makes them interesting enzyme candidates with enormous industrial potential. Unfortunately, they cannot be fully utilized due to their complex characteristic like their necessity of a cytochrome P450 reductase (CPR) for the electron transfer from NADPH. Furthermore, the P450s and CPRs contain membrane anchors leading to insoluble protein. These two factors represent challenges for their artificial production and consequently purification and whole-cell applications.The aim of this study was to overcome those challenges by construction of P450-fusion enzymes. Those fusion enzymes were designed based on the bacterial CYP102A (BM3) from Bacillus megaterium, which is a known natural fusion enzyme and does not possess any membrane anchor. Our fusion enzymes are composed of a changeable insect P450, a variable BM3 linker, BM3 CPR (BMR) and a C-terminal 6xHis-tag. For the first time, three different insect fusion enzymes of the CYP6 family (CYP6A1-BMR, CYP6G1-BMR and CYP6AE14-BMR) and of the CYP4G subfamily (CYP4G1-BMR, CYP4G2-BMR and CYP4GF-BMR) were constructed. Such a fusion made it possible to produce insect CYP6s recombinantly in an Escherichia coli system and to purify those without the use of detergents. Suitable LC- and GC-MS methods to characterize the purified enzymes were established in order to verify their ability to oxygenize the substrates imidacloprid and aldrin.A whole-cell approach was established to exclude the purification process as reason of CYP6-BMR construct inactivity. In this study it was shown that acyl-ACP reductase and aldehyde decarbonylase from the blue algae Nostoc punctiforme can be produced recombinantly in E. coli. It was demonstrated that they are able to catalyze the transformation of E. coli produced long-chain fatty acids to long-chain alkanes. In the next step the aldehyde decarbonylase was replaced by the CYP4G fusion constructs. Thereby the acyl-ACP reductase and the fusion construct generate a whole-cell system for alkane production. For the aldehyde and alkane detection a SPME-GC-MS method was established.The findings of the present study concerning the construction of novel insect P450-fusion enzymes as well as the established analytical methods serve as a basis for further insect P450 characterization and biocatalyst development.

Cytochrom-P450-Monooxygenasen (CYPs) bilden eine in vielen Organismen vorkommende Enzymgruppe mit einem großen Substratspektrum. Sie besitzen eine große Reaktionsvielfalt, wie zum Beispiel die Entgiftung von Insektiziden, was sie zu besonders interessanten Kandidaten für die industrielle Anwendung macht. Allerdings können CYPs auf Grund ihrer komplexen Eigenschaften, wie die Notwendigkeit einer Cytochrom-P450-Reduktase (CPR) für den Elektronentransfer von NADPH, nicht vollständig genutzt werden. Darüber hinaus sind CYPs und CPRs auf Grund ihrer Membrananker unlöslich. Diese zwei Faktoren stellen Herausforderungen für ihre artifizielle Produktion und anschließende Aufreinigungs- und Ganzzell-Anwendungen dar.Das Ziel dieser Studie war es, die genannten Schwierigkeiten durch die Konstruktion von CYP-Fusionsenzymen zu überwinden. Die Fusionsenzyme wurden auf Grundlage der bakteriellen CYP102A1 (BM3) aus Bacillus megaterium, einem natürlichen Fusionsenzym ohne Membrananker, konstruiert. Die generierten Fusionskonstrukte bestehen aus einer austauschbaren Insekten-CYP, einem variablen BM3-Linker, der BM3-CPR (BMR), und einem C-terminalem 6xHis-tag. Zum ersten Mal wurden drei verschiedene Insekten-Fusionsenzyme der CYP6-Familie (CYP6A1-BMR, CYP6G1-BMR und CYP6AE14-BMR) und der CYP4G-Unterfamilie (CYP4G1-BMR, CYP4G2-BMR und CYP4GF-BMR) konstruiert. Diese Fusion ermöglichte die rekombinante Insekten-CYP6-Produktion in Escherichia coli sowie die Aufreinigung ohne den Einsatz von Detergenzien. Mit dem Ziel die Fähigkeit der aufgereinigten Enzyme, die Oxidation der Substrate Imidacloprid und Aldrin, nachzuweisen, wurden passende LC- und GC-MS-Methoden für die Charakterisierung etabliert. Es wurde ein Ganzzell-Ansatz entwickelt, um den Aufreinigungsprozess als Grund für die CYP6-Inaktivität ausschließen zu können. In dieser Studie wurde gezeigt, dass die aus der Blaualge Nostoc punctiforme stammenden Enzyme Acyl-ACPReduktase und Aldehyddecarbonylase rekombinant zusammen in E. coli produziert werden können und, dass sie die von E. coli produzierten langkettigen Fettsäuren in langkettige Alkane umwandeln können. In einem nächsten Schritt wurde die Aldehyddecarbonylase durch ein CYP4G-Fusionskonstrukt ersetzt. Dadurch generieren die Acyl-ACP-Reduktase und das Fusionskonstrukt ein Ganzzell-System zur Alkanproduktion. Zur Detektion der Aldehyde und Alkane wurde eine SPME-GC-MS-Methode etabliert.Die Ergebnisse dieser Studie, welche die Konstruktion neuer Insekten-CYP-Fusionsenzyme, sowie die etablierten Methoden, dienen als Grundlage für die weitere Charakterisierung und biokatalytische Entwicklung von Insekten-CYPs.
Charakterisierung von neuen Insekten-Cytochrom-P450-Fusionsenzymen
Keywords: Cytochrom-P450-Monooxygenase; Insekten-CYP; Fusionsenzym; cytochrome P450 monooxygenase; insect P450; fusion enzyme; ddc:570